Microstructural and mechanical characterization of fiber laser welded quench-partitioning steels - Celik, Hafize; Saray, Onur (Walter De Gruyter Gmbh, 2025)
Advanced high-strength steels (AHSS) are increasingly used in the automotive industry for lightweight components due to their superior mechanical properties. Quench and partitioning (QP) steels provide an optimal balance between strength and formability, but their susceptibility to liquid metal embrittlement (LME) during resistance spot welding presents challenges. Laser welding, with its low heat input and high efficiency, offers a promising solution for reducing LME risks while ensuring strong, reliable joints for automotive applications. This study investigates the microstructural changes and mechanical performance of laser-welded joints between QP and dual phase (DP) steels. The fusion zone (FZ) and supercritical heat-affected zone (HAZ) primarily exhibited martensitic microstructures, while the midcritical and subcritical HAZ contained tempered martensite and ferrite on the DP side and a combination of tempered martensite, ferrite, and retained austenite on the QP side. These microstructural transformations contributed to enhanced FZ and HAZ regions, resulting in defect-free welds. Fractures occurred within the softer base metal (BM) regions, exhibiting ductile fracture characteristics without significant strength loss. However, joint ductility was slightly reduced compared to BMs due to strain localization caused by microstructure and thickness variations. The results demonstrate that laser welding is an effective method for joining QP steels in automotive manufacturing.
Keywords: advanced high-strength steels (AHSS); dual phase (DP) steels; fiber laser welding; mechanical and microstructural properties; quench - partitioning (QP) steels